Safety of epidural drugs: a narrative review. Issue 7 (3rd July 2019) - van Zuylen, ML; ten Hoope, W; Bos, EME; Hermanides, J; Stevens, MF; Hollmann, MW
ABSTRACT: Introduction : Epidural analgesia is a popular approach to postoperative and labor pain. Neurotoxicity and drug-specific systemic side effects can occur after epidural administration. As an increasing number of epidural drugs are studied and clinically applied, drug efficacy and safety evaluation are crucial. Areas covered : In this narrative review, the authors provide a thorough overview on the safety of the most widely used epidural drugs, focusing on potential neurotoxicity, side effects, and complications in the adult, non-pregnant population. A combined text and MeSH heading search strategy was used to identify relevant publications. Expert opinion : The search for the ideal epidural medication has resulted in a surplus of drug combinations with extensive heterogeneity amongst studies, while the value of investigating these is not always evident. Epidural drugs pose a potential threat of neurotoxicity and other side effects. Consequently, we should pursue safe epidural drug administration to patients and refrain from drugs with minimal proven benefit. Also, studies should compare epidural with systemic application. Because why use a drug epidurally, which can be safely used systemically? Future research should focus on providing solid evidence regarding efficacy of epidural analgesia compared to new and already existing modalities and optimizing presently used medicinal regimens.